PENGARUH PERPUTARAN KAS, PIUTANG DAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI (Terdaftar Di Bursa Efek Indonesia Periode 2017-2020) - Tifanni Tania; Hermawan Sutanto (STIE Atma Bhakti, 2021)
This study aims to determine whether cash turnover, accounts receivable turnover, and inventory turnover have an influence on profitability of companies in the consumer goods industry listed on the Indonesia Stock Exchange for the 2017-2020 period.The method of data collection is by tracing documents obtained from secondary data, namely financial reports downloaded from the IDX website. The population of companies in the consumer goods industry is the number of companies. The data analysis technique used is multiple linear regression analysis using SPSS version 21. The results of this test indicate that cash turnover and accounts receivable turnover have no partial effect on profitability, only inventory turnover has a positive and significant effect on profitability. At the same time, turnover cash, accounts receivable turnover, and inventory turnover have a significant effect on profitability with an effect size of 34.1%.